PENGGUNAAN POWER POINT DAN LEAFLEAT TERHADAP PENINGKATAN PENGETAHUAN SISWA KELAS IX TENTANG P3K DI SMP TUNAS KARYA BATANG KUIS TAHUN 2017 - Pangaribuan, Resmi; Pratama, Muchti Yuda (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Emergency conditions can occur anywhere, anytime and it is the duty of health workers to handle the problem. Death occurs usually because of the inability of health workers to deal with patients in the golden period. This effort must begin by correctly identifying the condition of the accident patient.This study aims to determine the effect of using power point and Leafleat on the knowledge of class IX students at SMP Tunas Karya Batang Kuis. The type of this research is Quasi experiment two group pretest-posttest. The total population in this study was first class IX First Class Middle School students in accidents (Firs Aid) of 110 people. The results of the research carried out statistically showed that power point and leafleat media influenced the increase in knowledge of class IX students on first aid (P3K). It is recommended for students to increase knowledge about first aid in accidents (Firs Aid) in helping victims who need emergency assistance immediately and are ready to use in urgent situations. To the leadership of the Foundation to take wisdom in health education, to increase the knowledge of students to hold first aid training on accidents (Firs Aid) and form the Youth Red Cross.